2022
DOI: 10.1007/s12649-022-01807-9
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafiltration of Fucus vesiculosus Extracts Under Different Operating Conditions

Abstract: The interest in separating and concentrating bioactives and minerals from seaweeds extracts is growing due to large health bene ts of these substances. The aim of this study was to investigate the separation of components of Fucus vesiculosus seaweed extracts by tangential ultra ltration and apply Hermia's models adapted to cross ow ultra ltration to understand the fouling mechanism. The in uence of membrane cut-off varying from 5 to 150 kDa, cross ow velocity from 0.081 and 0.095 m/s and transmembrane pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…For instance, the performed membrane cleaning allowed the flux to increase to 130 L/m 2 h under a TMP of 0.4 MPa, while the initial flux was equal to 240 L/m 2 h. Worthy of note, repeating the membrane cleaning operation increased the maximum flux to 170 L/m 2 h. Based on this finding, it can be concluded that, after the filtration of real solutions, the maximum performance of the membranes irretrievably stabilized at a lower level than that noted for the new membranes. Based on the literature review, it should be noted that the P3 Ultrasil 11 solution has been widely used as a chemical cleaning agent for UF membranes fouled with components of various feed solutions, such as oily wastewaters [ 12 , 30 ], separated digestate [ 39 ], orange juice [ 40 , 41 ], Fucus vesiculosus extracts [ 42 ] and spent sulfite liquor [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the performed membrane cleaning allowed the flux to increase to 130 L/m 2 h under a TMP of 0.4 MPa, while the initial flux was equal to 240 L/m 2 h. Worthy of note, repeating the membrane cleaning operation increased the maximum flux to 170 L/m 2 h. Based on this finding, it can be concluded that, after the filtration of real solutions, the maximum performance of the membranes irretrievably stabilized at a lower level than that noted for the new membranes. Based on the literature review, it should be noted that the P3 Ultrasil 11 solution has been widely used as a chemical cleaning agent for UF membranes fouled with components of various feed solutions, such as oily wastewaters [ 12 , 30 ], separated digestate [ 39 ], orange juice [ 40 , 41 ], Fucus vesiculosus extracts [ 42 ] and spent sulfite liquor [ 43 ].…”
Section: Resultsmentioning
confidence: 99%